1996
DOI: 10.1111/j.1365-2605.1996.tb00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromomycin A3‐staining as an indicator of protamine deficiency and fertilization

Abstract: Mature mammalian spermatozoa have a compact and stable nuclear structure conferred by protamines instead of histones, which are present in all other cellular types. Chromomycin A3 (CMA3) is a useful tool for the detection of protamine deficiency in sperm chromatin. The purpose of this study was to correlate the percentage of spermatozoa staining positively for CMA3 with sperm parameters and in-vitro fertilization of human oocytes. Spermatozoa were collected from 56 fertile and 18 infertile men, and washed twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 12 publications
6
72
0
Order By: Relevance
“…Neither Lolis et al (1996) nor found a significant change in CMA 3 staining following swim-up preparation, confirming the absence of a relationship between CMA 3 staining and motility. However, a significant decrease in CMA 3 staining was reported following density gradient centrifugation by , although not by Lolis et al (1996). The decrease in CMA 3 staining is somewhat intuitive due to the selection of highly condensed spermatozoa by density gradient preparations.…”
Section: Assessment Of Sperm Chromatin Structure In Fertility Evaluatmentioning
confidence: 91%
See 2 more Smart Citations
“…Neither Lolis et al (1996) nor found a significant change in CMA 3 staining following swim-up preparation, confirming the absence of a relationship between CMA 3 staining and motility. However, a significant decrease in CMA 3 staining was reported following density gradient centrifugation by , although not by Lolis et al (1996). The decrease in CMA 3 staining is somewhat intuitive due to the selection of highly condensed spermatozoa by density gradient preparations.…”
Section: Assessment Of Sperm Chromatin Structure In Fertility Evaluatmentioning
confidence: 91%
“…These results indicate that a high percentage of morphologically normal spermatozoa may have hidden abnormalities in chromatin structure. However, no clear cutoff value for infertility has been demonstrated (Lolis et al, 1996). While one study reported an association between CMA 3 staining and fertilization ability following SUZI, this was not found in routine IVF or ICSI .…”
Section: Assessment Of Sperm Chromatin Structure In Fertility Evaluatmentioning
confidence: 92%
See 1 more Smart Citation
“…Condensation of spermatid chromatin is accompanied by replacement of histones with protamines, which are basic nuclear proteins with a high Cys content, as well as by subsequent oxidation of protamine thiol groups to form disulfide linkages that result in protein crosslinking (32,34). The chromatin of sperm is highly compacted to protect the DNA from deleterious environments with insufficient oxidation of protamine thiol groups being associated with damage to sperm DNA (35)(36)(37). The reduction of sperm disulfides followed by decondensation of sperm chromatin in readiness for fertilization is accomplished in oocytes, which contain high levels of glutathione (38).…”
Section: Discussionmentioning
confidence: 99%
“…The CMA3 assay is becoming more extensively used for evaluating sperm quality as part of male fertility assessment (52,53). It provides an indirect measure of assessing protamines in sperm (54,55), where CMA3 competes with protamines for chromatin binding (47,56).…”
Section: Zubkova Effect Of Age On Spermatozoal Chromatin Fertil Stementioning
confidence: 99%